Figures of possibility: aesthetic experience, mysticism, and the play of the senses - Largier, Niklaus (Cultural memory in the present, 2022)
Disruptions -- Figuration -- Reweaving perception -- Imitation -- Framings -- Monadic transcriptions -- Modernist moments -- Holy fools.